2021
DOI: 10.31392/npu-nc.series15.2021.7(138).16
|View full text |Cite
|
Sign up to set email alerts
|

Fitness training as the mean of improving the physical fitness of high skilled football players

Abstract: The results of physical fitness level of highly skilled football players in the preparatory and competitive periods of the annual macrocycle are presented. The study involved 34 players of Football Club “Zorya” (Lugansk city) aging from 20 to 30. In the annual cycle of football players training season 2018/2019, the training process was carried out in accordance with the current program. An experimental program was used in the first and second preparatory periods of the annual training cycle in the season 2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Previous studies reported that technology in the sports sector is a complex system for collecting and processing large amounts of data (Camomilla, Bergamini, Fantozzi, & Vannozzi, 2018;Ratten, 2020). It aims to improve sports performance, where its use has been proven effective in sports training (Firdaus & Mario, 2022;Handayani et al, 2023;Kokarev, Kokareva, Atamanuk, Terehina, & Putrov, 2023;Lisenchuk et al, 2023;Oh, Johnson, & Syrop, 2019). Another study reported that sensor technology benefits transparent and objective measurement results (Eitzen, Renberg, & Faerevik, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that technology in the sports sector is a complex system for collecting and processing large amounts of data (Camomilla, Bergamini, Fantozzi, & Vannozzi, 2018;Ratten, 2020). It aims to improve sports performance, where its use has been proven effective in sports training (Firdaus & Mario, 2022;Handayani et al, 2023;Kokarev, Kokareva, Atamanuk, Terehina, & Putrov, 2023;Lisenchuk et al, 2023;Oh, Johnson, & Syrop, 2019). Another study reported that sensor technology benefits transparent and objective measurement results (Eitzen, Renberg, & Faerevik, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is an opportunity to simultaneously develop different qualities. If different training influences are combined based on certain rules, and the priorities are correctly set during the selection of goals and tasks, it is possible to favorably influence the simultaneous development of various physical qualities [8]. Therefore, it is necessary for the coach to familiarize his individual with this phenomenon in an accessible form and jointly decide on priorities [11].…”
Section: науковий часопис нпу імені м п драгоманова Dragomanov Ukrain...mentioning
confidence: 99%